"Boundaries" and "thresholds": Conceptual models of the musical mind in the history of music psychology. (September 2014) - Kim, Youn
The mutual relationship between German psychology and music theory in the late 19th century has been generally understood within the context of the positivist movement of this same time period. Studies of both the mind and music had been recently institutionalized as independent academic disciplines, both aspiring to be scientific. What might be more significant, however, than this shared aspiration is the change in the conception of the human mind itself: The question to be addressed is how the human psyche, the agency of musical listening, was conceptualized with the advent of new perspectives in mind science. Focusing on the conceptual rather than methodological dimension of interdisciplinarity, the present article looks into the selected writings of pioneers in the psychology of music including Hugo Riemann, Johann Friedrich Herbart, Wilhelm Wundt, and Gustav Fechner. A closer inspection of the use of technical terms such as Vorstellungen and Tonvorstellungen reveals a flux between different psychological conceptualizations that can be characterized by ideas such as "boundary" and "threshold." The notions of the human psyche fluctuated between mind ( Geist ) and soul ( Seele ) – to borrow Edward Reed's expression – and this conceptual change possibly points to an important paradigmatic shift in early music psychology.